Notary Liability Examined by Investigators in Criminal Actions of False Information on Authentic Deed - Jhon Eddy; Ahmad Sudiro (Global Writing Academica Researching and Publishing, 2022)
To provide clarity, order, and legal protection, it is essential to have authentic written documentation of acts, agreements, stipulations, and legal events performed by or before an authorized official. Laws and rules are necessary for authentic deeds in order to establish clarity, order, and legal protection. Society need a notary who is dependable, trustworthy, whose signature and all stamps give assurances and evidence, an impartial expert and advisor who is faultless (onkreukbaar or unimpeachable), keeps his mouth shut, and enters into an agreement that will protect him in the future. The purpose of the implementation of this research is to see how the form of notary accountability in the crime of giving false information for authentic deeds. This research will be conducted using a qualitative approach and normative juridical methods. The results of this study found that the research method used was a normative juridical research method. The responsibilities of a Notary can be divided into Civil Liability, Criminal Liability, and Administrative Responsibilities. This MKN institution has an essential role in replacing the MPD’s part. MKN has the authority to approve the police, public prosecutors, and judges to examine notaries, only formed in 2016.